An Approach to Diagnostic Criteria for the Definition of Slight Cognitive Impairment - Julio Armas Castro; Mayra Rosa Carrasco García; Sussette Angell Valdés; Yanet López Mena (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
For years the term slight cognitive impairment has been used in literature as a transitional stage between normal aging and a slight Alzheimer's disease and in conversion studies it has been associated to quantitative and qualitative alterations that support that support the hypothesis that slight cognitive impairment constitutes an early stage of dementia in most of the patients. In this search the most updated diagnostic criteria on the topic have been reviewed looking for both a diagnostic consensus among the multiple and heterogeneous symptoms of this disorder and a clear, concise and uniform criterion that allow to reach a right definition and diagnosis of patients with slight cognitive impairment.